Particle swarm optimization-based stator resistance observer for speed sensorless induction motor drive - Ho, Sang Dang; Palacky, Petr; Kuchar, Martin; Brandstetter, Pavel; Tran, Cuong Dinh (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper presents a different technique for the online stator resistance estimation using a particle swarm optimization (PSO) based algorithm for rotor flux oriented control schemes of induction motor drives without a rotor speed sensor. First, a conventional proportional-integral controller-based stator resistance estimation technique is used for a speed sensorless control scheme with two different model reference adaptive system (MRAS) concepts. Finally, a novel method for the stator resistance estimation based on the PSO algorithm is presented for the two MRAS-type observers. Simulation results in the Matlab/Simulink environment show good adaptability of the proposed estimation model while the stator resistance is varied to 200% of the nominal value. The results also confirm more accurate stator resistance and rotor speed estimation in comparison with the conventional technique.